PERSEPSI GURU TENTANG PENGEMBANGAN MODEL PEMBELAJARAN LITERASI FOKUS MENULIS NARASI DENGAN TEKNIK PROBING-PROMPTING DI SD - Alif Mudiono; Suhel Madyono (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2014)
Abstract: Developing model of literacy teaching narration writing focused with a probing-prompting technique in elementary schools. Purpose of the research was to describe teachers’ knowledge toward teaching models, teaching materials, and teachers’ perception about of an implementation model of literacy teaching narration writing focused with a probing-prompting technique in elementary schools. The data sources were description about model of literacy teaching, teaching materials, andteachersperception of implementation model of literacy teaching narration writing focused in elementary school. On the basis of data analysis, results showed teachers’ knowledge toward literacy teaching where 28.34% very positive and 63.17% positive. Teaching materials needed were 15.22% very positive and 51.11% positive, and teachers’ perception toward teaching models were 11.53 very positive and 28.47 % positive.Keywords: model, literacy, probing-prompting, elementary schoolAbstrak: Penelitian ini bertujuan mendeskripsikan pengetahuan guru tentang model pembelajaran, bahan pembelajaran, dan persepsi guru tentang model pelaksanaan pembelajaran literasi fokus menulis narasi dengan Teknik Probing-Prompting di SD. Sumber data berupa deskripsi tentang model pembelajaran literasi, bahan pembelajaran, dan persepsi guru tentang pelaksanaan model pembelajaran literasi fokus menulis narasi di SD. Berdasarkan analisis data diperoleh temuan pengetahuan guru tentang model pembelajaran literasi sebesar 28,34 sangat positif dan 63,17% kategori positif, bahan pembelajaran yang dibutuhkan sebesar 15,22% kategori sangat positif dan 51,11% kategori positif, dan persepsi guru tentang model pelaksanaan pembelajaran sebesar 11,53 % kategori sangat positif dan 28,47% kategori positif. Kata Kunci: model, literasi, probing-promting, SD